Effect of Extended‐Release Niacin on High‐Density Lipoprotein (HDL) Functionality, Lipoprotein Metabolism, and Mediators of Vascular Inflammation in Statin‐Treated Patients. Issue 9 (15th September 2015) - Yadav, Rahul; Liu, Yifen; Kwok, See; Hama, Salam; France, Michael; Eatough, Ruth; Pemberton, Phil; Schofield, Jonathan; Siahmansur, Tarza J.; Malik, Rayaz; Ammori, Basil A.; Issa, Basil; et al.
Abstract : Background: The aim of this study was to explore the influence of extended‐release niacin/laropiprant (ERN/LRP) versus placebo on high‐density lipoprotein (HDL) antioxidant function, cholesterol efflux, apolipoprotein B100 (apoB)‐containing lipoproteins, and mediators of vascular inflammation associated with 15% increase in high‐density lipoprotein cholesterol (HDL‐C). Study patients had persistent dyslipidemia despite receiving high‐dose statin treatment. Methods and Results: In a randomized double‐blind, placebo‐controlled, crossover trial, we compared the effect of ERN/LRP with placebo in 27 statin‐treated dyslipidemic patients who had not achieved National Cholesterol Education Program‐ATP III targets for low‐density lipoprotein cholesterol (LDL‐C). We measured fasting lipid profile, apolipoproteins, cholesteryl ester transfer protein (CETP) activity, paraoxonase 1 (PON1) activity, small dense LDL apoB (sdLDL‐apoB), oxidized LDL (oxLDL), glycated apoB (glyc‐apoB), lipoprotein phospholipase A2 (Lp‐PLA2), lysophosphatidyl choline (lyso‐PC), macrophage chemoattractant protein (MCP1), serum amyloid A (SAA) and myeloperoxidase (MPO). We also examined the capacity of HDL to protect LDL from in vitro oxidation and the percentage cholesterol efflux mediated by apoB depleted serum. ERN/LRP was associated with an 18% increase in HDL‐C levels compared to placebo (1.55 versus 1.31 mmol/L, P <0.0001). There were significant reductions in total cholesterol, triglycerides, LDL cholesterol, total serum apoB, lipoprotein (a), CETP activity, oxLDL, Lp‐PLA2, lyso‐PC, MCP1, and SAA, but no significant changes in glyc‐apoB or sdLDL‐apoB concentration. There was a modest increase in cholesterol efflux function of HDL (19.5%, P =0.045), but no change in the antioxidant capacity of HDL in vitro or PON1 activity. Conclusions: ERN/LRP reduces LDL‐associated mediators of vascular inflammation, but has varied effects on HDL functionality and LDL quality, which may counter its HDL‐C‐raising effect. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01054508.